PENERAPAN KEADILAN RESTORATIF DALAM TINDAK PIDANA PENADAHAN (Solusi, 2023)
Restorative justice is the settlement of criminal acts by involving perpetrators, victims, families of victims/perpetrators, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. The perpetrators of the crime of fencing which are threatened with Article 480 of the Criminal Code can be applied to restorative justice. The application of the criminal act of fencing can be carried out as long as it fulfills the requirements in the application of restorative justice, namely the suspect is the first time to commit a crime; criminal acts are only punishable by fines or threatened with imprisonment of not more than 5 (five) years; and the crime is committed with the value of the evidence or the value of the loss incurred is not more than Rp. 2,500,000.- (two million five hundred thousand rupiah).